ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL BRUTO, TINGKAT UPAH MINIMUM KOTA, TINGKAT INFLASI DAN BEBAN/TANGGUNGAN PENDUDUK TERHADAP PENGANGGURAN TERBUKA DI KOTA MAGELANG PERIODE TAHUN 1990 â€“ 2010 - Sis Putro, Akbar; Hendra Setiawan, Achma (Diponegoro Journal of Economics, 2013)
Economic growth is a measure of the success of economic development of a region. Economic development of a region can be seen from several economic indicators, one of Â them is the level of unemployment. Increase in population led to rising labor force, but it is not matched with adequate number of jobs that have an impact on the growing number of unemployed. In the city of Magelang unemployment is quite high compared with cities and other districts in Central Java, which reached 13.28 percent in 2010.The purpose of the of the study was the analyze the influence of GDP, wages, inflation, and Dependency Ratio on the enemployment rate in Magelang and analyze the factors that most strongly influence the level of unemployment in Magelang in 1990-2010. The data used are time series of quantitative secondary data obtained from the BPS during the period 1990-2010. Regression model used is the method of multiple linear regression analysis.Based on the results of tests per out formed with simultaneous test (F test) show that overall the independent variables (GDP, inflation, wages, and Dependency Ratio) together have significant effect on the level of unemployment that occurred in Magelang. The value of R2 amounting to 0,556 which means 55,6 percent is explanatory to the dependent variable (unemployment rate), while the remaining 44,4 percent is explained by other variables outside of the model used.